2023
DOI: 10.1200/jco.23.00697
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Interventions to Promote Adjuvant Endocrine Therapy Adherence Among Breast Cancer Survivors

Abstract: PURPOSE Adjuvant endocrine therapy (AET) adherence among breast cancer survivors is often suboptimal, leading to higher cancer recurrence and mortality. Intervention studies to promote AET adherence have burgeoned, more than doubling in number since this literature was last reviewed. The current aim is to provide an up-to-date systematic review and meta-analysis of interventions to enhance AET adherence and to identify strengths and limitations of existing interventions to inform future research and clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Specific medications that appeared to increase the risk of declining adherence included psycholeptics, psychoanaleptics, and analgesics. In a recent systematic review of AET adherence interventions, some approaches, such as psychosocial and reminder interventions, had some promise in promoting adherence [ 36 ]. However, the authors concluded that more powerful approaches would be needed to improve efficacy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific medications that appeared to increase the risk of declining adherence included psycholeptics, psychoanaleptics, and analgesics. In a recent systematic review of AET adherence interventions, some approaches, such as psychosocial and reminder interventions, had some promise in promoting adherence [ 36 ]. However, the authors concluded that more powerful approaches would be needed to improve efficacy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review of AET adherence interventions, some approaches, such as psychosocial and reminder interventions, had some promise in promoting adherence [ 36 ]. However, the authors concluded that more powerful approaches would be needed to improve efficacy [ 36 ]. Our study provides further evidence of the subgroups of women who may benefit the most from these types of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that there are significant knowledge gaps in this area as we do not yet have an effective educational intervention for teaching patients about adjuvant endocrine therapy, we do not know if an educational intervention will improve adherence as this research is limited and thus outcomes are not known [ 57 ]. Other interventions to improve adherence of adjuvant endocrine therapy have had modest success and thus improving adherence in this patient population is possible and thus worth pursing [ 58 ]. Research is needed to develop an easy to implement adjuvant endocrine therapy educational intervention that would improve adherence and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3,[10][11][12] These interventions often focus on educating women about AET. 13 Education may be essential, but insufficient by itself in helping women navigate the broader emotional and psychological challenges that occur with side-effects which undermine adherence. AET side effects may present tangible and distressing reminders of cancer, at a time when women are expecting to return to the life they experienced before diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Existing interventions for supporting adherence to AET are mostly ineffective 3,10–12 . These interventions often focus on educating women about AET 13 . Education may be essential, but insufficient by itself in helping women navigate the broader emotional and psychological challenges that occur with side‐effects which undermine adherence.…”
Section: Introductionmentioning
confidence: 99%